ANALISIS CAPITAL INTENSITY & NET PROFIT MARGIN TERHADAP EFFECTIVE TAX RATE - Dwinta Mulyanti; Gabrilfani Sundawa (Jurnal Financia : Akuntansi dan Keuangan, 2022)
The effective tax rate is used as a reference used by companies to make decisions by interested parties to make policies within the company on the tax system. This study aims to test whether capital intensity and net profit margin affect the effective tax rate at the PT Jaya Fermex company, this test is carried out on the food sub-sector company in the form of baking solution. The data used is secondary data obtained directly from the PT Jaya Fermex Company for the period 2017 to 2020. This research method is quantitative with a descriptive verification approach. Descriptive verification method is used to determine whether there is an effect of the variables raised in the study and to verify the research results obtained with relevant previous studies. The results partially show that capital intensity has no effect on the Effective Tax Rate, while the net profit margin has a significant effect on the Effective Tax Rate. And the results simultaneously show that capital intensity and net profit margin have a significant effect on the Effective Tax Rate.